Creative business in the mindset of PGSD University PGRI Palembang students towards an interest in entrepreneurship - Zamhari, Ahmad; Uswatun Hasanah, Ummy; Moutia Asmini , Rahma; Safinatunnaja, Safinatunnaja; Fashohati Rozanah , Wafiq (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2024)
In order to fulfill the desire for entrepreneurship in tertiary institutions, a mindset is needed for PGSD students, so that students can have knowledge and skills. The mindset and entrepreneurial spirit of students can ultimately foster student entrepreneurial interest. The formulation of the problem is how students think in creative endeavors. The aim is to find out the mindset of PGSD students at PGRI Palembang University towards their interest in creative endeavors. The research method used is descriptive qualitative. With data collection techniques using a questionnaire via Google Form to second semester PGSD students. The results of this study indicate that entrepreneurship education, entrepreneurial mindset, and creativity have a positive and significant effect on students' creative business mindset in entrepreneurial intentions in PGSD University PGRI Palembang students.